Studi Literatur: Analisis Keamanan dan Privasi Data Rekam Medis Elektronik Fasilitas Pelayanan Kesehatan Berdasarkan UU Nomor 27 Tahun 2022 - Adelia Inggrid Putri Maharani; Sinta Novratilova; Azalia Tjandra Dewi; Dwi Rena Aulia; Rina Wulandari; Aldi Juli Saputra (Pusat Riset dan Inovasi Nasional, 2026)
Systemic non-compliance with PERMENKES 24/2022 & UU PDP 27/2022 on EHR, such as human error, weak passwords, vulnerable physical access, and low ISO 27001, increases the risk of data breaches & fines. This research fills the gap in the study by evaluating the compliance of the CIA Triad principles on Electronic Medical Records post-issuance of PERMENKES No. 24 of 2022 and Law No. 27 of 2022 thru a literature review, while also highlighting the impact of non-compliance on service quality and patient trust. This study aims to evaluate the compliance of healthcare facility security systems with PERMENKES No. 24 of 2022 and Law No. 27 of 2022 and analyze the impact of non-compliance on service quality and patient trust. This research method employs a systematic narrative literature review design to comprehensively examine the implementation of the CIA Triad in EHR security. Searches were conducted on Google Scholar (2023-2026) using the keywords